Natural Language Understanding Using Open Information Extraction Technique - Zadgaonkar, Ashwini V (International Journal of Computer Sciences and Engineering, 2025)
Natural language understanding (NLU) task deals with use of computer software to understand human text or speech in the form of sentences. IE is the integral component of this task. IE extracts information about desired entities from diverse resources and stored it in machine readable format for future processing. IE systems developed so far uses either supervised or unsupervised approach for information extraction. Distant supervision, Open information extraction and Joint prediction are few more techniques which claims to improve IE system performance. This paper is an attempt to give comparative analysis of these advanced approached and the need of combination of these techniques for further enhancement. To conclude, few application areas were identified like machine reading which can be benefited from this combined approach.